Mobile Genetic Elements Harboring Antibiotic Resistance Determinants in Acinetobacter baumannii Isolates From Bolivia - Cerezales, Mónica; Xanthopoulou, Kyriaki; Wille, Julia; Krut, Oleg; Seifert, Harald; Gallego, Lucía; Higgins, Paul G. (Frontiers in Microbiology, 2020)
Using a combination of short- and long-read DNA sequencing, we have investigated the location of antibiotic resistance genes and characterised mobile genetic elements in three clinical multi-drug resistant Acinetobacter baumannii. The isolates, collected in Bolivia, clustered separately with three different international clonal lineages. We found a diverse array of transposons, plasmids and resistance islands related to different IS elements, which were located in both the chromosome and in plasmids, which conferred resistance to multiple antimicrobials, including carbapenems. Carbapenem resistance might be caused by a Tn2008 carrying the blaOXA-23 gene. Some plasmids were shared between the isolates. Larger plasmids were less conserved than smaller ones and they shared some homologous regions, while others were more diverse, suggesting that these big plasmids are more plastic than the smaller ones. The genetic basis of antimicrobial resistance in Bolivia has not been deeply studied until now, and the mobilome of these A. baumannii isolates, combined with their multi-drug resistant phenotype, mirror the transfer and prevalence of mobile genetic elements contributing to the spread of antibiotic resistance worldwide and require special attention. These findings could be useul to understand the antimicrobial resistance genetics of A. baumannii in Bolivia and the difficulty in tackling these infections.